Applying healthcare systems engineering methods to the patient discharge process. (3rd February 2011) - Farris, Jennifer A.; Matis, Timothy I.; McAllister, Marlene; Snider, Alan
The patient discharge process has been a perennial problem for hospitals of all sizes. Four decades worth of research have resulted in many insights for improving the quality of the process, but fewer breakthroughs regarding improving the speed of the process. Meanwhile, the timing of patient discharges is a key constraint on hospital capacity. Specifically, achieving better control over the discharge process may help hospitals alleviate one of their most severe capacity issues: gridlock in the emergency room. This paper presents results from a case study in a 362-bed regional teaching hospital in Texas, USA, where healthcare systems engineering methods were applied to document the current state of the discharge process and identify the most significant root causes of delays. Directions for future research on the design and management of the patient discharge process are identified and discussed, based on the case study findings and the literature review of previous work on patient discharge planning.